Answer:
converts Celsius to Fahrenheit.
converts Fahrenheit to Celsius.
Step-by-step explanation:
Write given data in the table
Let the expression for the function be
Note, that this equation is linear equation and it is well-known fact that the Celsius to Fahrenheit dependence is linear.
Substitute corresponding values into this expression:
Subtract these two equations:
Substitute it into the first equation:
So,
This is the function which converts Celsius to Fahrenheit.
And function
converts Fahrenheit to Celsius.
Answer:
7. x=19 2x=38
8.x=23 3x=69
9.x=12 (50-2)/4=12
10.x=15 (31-1)/2
11.x=16 (84-4)/5
12.x=27 (55-1)/2
Step-by-step explanation:
if 2 angles are opposite, it's the same
Answer:
<AFB
Step-by-step explanation: